Bimbingan Teknis Perencanaan Pembangunan dan Anggaran Desa - Pudjianto, S.Y.; Triyono, Joko; Eka, Agus; Sikwan, Agus; Marini (JPM: Jurnal Pengabdian Masyarakat, 2024)
A village as a government organization that has a strategic role in the implementation of development, because the village deals directly with people with all backgrounds needs and interests. Many policies must be implemented by the village government, so there are still often misperceptions caused by the still weak human resources in the village government, resulting in timely demands in budget use accountability reports that cannot be achieved. This condition also occurs in Mempawah Regency, there are still many villages that do not fully understand development planning and village financial management properly, one of which is a village in Mempawah Hilir District. This PKM aims to through technical guidance provide an understanding of village development planning by the needs of the community and the potential that exists in the village, as well as village financial management. The methods used in PKM are participatory and instructional approaches. The results obtained in the implementation of PKM are that participants gain understanding and information on the importance of village development planning, and the process of village financial management to accountability, also at the same time can complete village financial accountability reports in the current year and can compile development plans and activities and the RAPBDes for the next year can be compiled properly.